Effects of sulfate reduction processes on the trace element geochemistry of sedimentary pyrite in modern seep environments. (15th September 2022) - Lin, Zhiyong; Sun, Xiaoming; Chen, Kaiyun; Strauss, Harald; Klemd, Reiner; Smrzka, Daniel; Chen, Tingting; Lu, Yang; Peckmann, Jörn
Abstract: Although it has been suggested that the trace element patterns of sedimentary pyrite can be affected by early diagenesis, detailed studies on modern marine environments addressing this hypothesis are scarce. Organoclastic sulfate reduction (OSR) and sulfate-driven anaerobic oxidation of methane (SD-AOM) are the dominant sulfate reduction processes in organic-rich and methane-rich marine sediments, and commonly result in the formation of authigenic pyrite. To better understand how OSR and SD-AOM affect the trace element geochemistry of pyrite, we applied laser ablation – inductively coupled plasma – mass spectrometry (LA-ICP-MS) to analyze trace element contents of pyrite from two methane-seep sites (DH-CL11 and HS148) of the South China Sea. The trace element data are complemented by the measurement of iron isotope compositions of authigenic pyrite. This new data set, supplemented by published sulfur isotope data, improves our understanding of the diagenetic processes during early diagenetic pyrite formation. High δ 56 Fe and δ 34 S values of pyrite reflect the dominance of SD-AOM within sulfate-methane transition zones (SMTZs) at both sites (i.e., from 705 to 767 cm below seafloor at site DH-CL11 and from 490 to 690 cm below seafloor at site HS148), whereas pyrite from shallow depth characterized by low δ 56 Fe values points to early OSR processes. Within the SMTZs, pyrite exhibits highly variable but overall high manganese (Mn) contents (12 to 732 mg/kg at site DH-CL11; 12 to 1145 mg/kg at site HS148), compared to OSR-derived pyrite from shallow depth. Similar to this pattern, pyrite formed at the SMTZ shows higher lead (Pb), zinc (Zn), copper (Cu), and vanadium (V) contents than pyrite formed at shallower depths above the SMTZ. Enrichments of these metals in pyrite forming at the SMTZ are best explained by enhanced reductive dissolution of iron and manganese (oxyhydr)oxides under sulfidic conditions induced by SD-AOM, and subsequent trace element incorporation into pyrite. Arsenic (As), molybdenum (Mo), and antimony (Sb) distributions in pyrite vary between the two study sites. Pyrite from shallow depth of site HS148 has high contents of all three elements, indicating effective immobilization of dissolved As, Mo, and Sb during pronounced OSR. In contrast, apparently less intense OSR at shallow depth of site DH-CL11 allowed for more dissolved As, Mo, and Sb to diffuse downward to greater depth, resulting in the enrichments of these elements in pyrite formed at or close to the SMTZ. Positive correlations between As and cobalt (Co), and between As and nickel (Ni) typify pyrite derived from both OSR and SD-AOM for both study sites, and As-rich pyrite from site DH-CL11 is characterized by a distinctly high Co/Ni ratio. Both patterns suggest that the presence of As affects the uptake of Co and Ni into pyrite. Our study documents that pyrite element contents in methane-rich environments are significantly influenced by different sulfate reduction processes during early diagenesis, allowing the differentiation of OSR-derived pyrite from SD-AOM-derived pyrite by means of trace element geochemistry.